2015
DOI: 10.3390/e17106598
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Detection of Scatterer Concentration by Weighted Entropy

Abstract: Abstract:Ultrasound backscattering signals depend on the microstructures of tissues. Some studies have applied Shannon entropy to analyze the uncertainty of raw radiofrequency (RF) data. However, we found that the sensitivity of entropy in detecting various scatterer concentrations is limited; thus, we propose a weighted entropy as a new information entropy-based approach to enhance the performance of scatterer characterization. A standard simulation model of ultrasound backscattering was used to generate back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…It has been shown that entropy estimated using the probability distribution of ultrasound signals is proportional to ultrasound statistical parameters, and therefore it is expected to inherit the properties of statistical parameters, such as the dependencies of number density of scatterers, attenuation, noise, frequency, transducer focusing, and other factors that affect the size of the resolution cell43. The effects of number density of scatterers on entropy were discussed in the previous paragraph.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that entropy estimated using the probability distribution of ultrasound signals is proportional to ultrasound statistical parameters, and therefore it is expected to inherit the properties of statistical parameters, such as the dependencies of number density of scatterers, attenuation, noise, frequency, transducer focusing, and other factors that affect the size of the resolution cell43. The effects of number density of scatterers on entropy were discussed in the previous paragraph.…”
Section: Discussionmentioning
confidence: 99%
“…For healthy women, dense fibroglandular tissues are more common, and the corresponding density in a breast parenchyma decreases with age48. Ideally, a normal breast parenchyma based on fibroglandular tissues causes a fully developed speckle pattern in the B-mode image, which corresponds to the envelope statistics of the Rayleigh distribution43. Compared with normal breast tissue, benign fibroadenoma is composed of glandular tissues and local fibrous tissues or calcification49.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the scatterer concentration, not only generates a stronger effect of constructive wave interference to cause the echo amplitude distribution to vary toward the Rayleigh distribution [46], but also leads to a larger backscattered amplitude [47,48]. In this condition, various echo amplitudes exist, and the signal uncertainty and unpredictability (entropy) increase [33].…”
Section: Effects Of Fatty Infiltration On Ultrasound Entropymentioning
confidence: 99%
“…From this point of view, non-model-based parameters that can be calculated using any type of data irrespective of the data distribution are suggested as alternatives for characterizing tissues. Among non-model-based statistical parameters, entropy has been shown to correlate with the parameters of the statistical models and the envelope statistics [33], which is a useful clue for characterizing fatty liver [27,28]. Recall that Shannon established information theory and defined entropy as a measure of information uncertainty [34].…”
Section: Introductionmentioning
confidence: 99%